Case Report: Ibu Hamil Grande Multigravida Trimester Ii Resiko Tinggi - Revalina Anissa Azzahra; Astuti Setiyani; Suparji Suparji; Nana Usnawati Suparji (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Introduction: Very High-Risk Pregnancy (KRST) increases the likelihood of maternal and fetal complications. Risk factors include advanced maternal age, grande multigravida, an interpregnancy interval, previous Cesarean sections, and non-use of postpartum contraception. This case report aimed to describe midwifery care for a woman with KRST. Methods: A case report using the SOAP approach was conducted on a 36-year-old pregnant woman (G6P30023) in her second trimester with grande multigravida, an 18-month interpregnancy interval, and no postpartum contraception. Care was provided over one month through five visits. Data were collected through interviews, observation, physical examination, and documentation review. Results: Comprehensive care, including maternal-fetal monitoring, nutritional education, iron (Fe) and MMS administration, and postpartum contraception counseling, maintained stable maternal and fetal conditions without complications while improving maternal knowledge and readiness to use postpartum contraception. Conclusion: Comprehensive and continuous midwifery care maintained maternal and fetal health and minimized the risk of complications in KRST.